2014
DOI: 10.1016/j.ridd.2013.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of muscle fat infiltration in children with spina bifida

Abstract: Children with spina bifida have well recognized functional deficits of muscle, but little is known about the associated changes in muscle anatomy and composition. This study used water-fat magnetic resonance imaging (MRI) to measure fat infiltration in the lower extremity muscles of 11 children with myelomeningocele, the most severe form of spina bifida. MRI measurements of muscle fat fraction (FF) were compared against manual muscle test (MMT) scores for muscle strength. The FF measurements were objective and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
4
1
Order By: Relevance
“…4 This is not surprising because myelomeningocele predominantly affects the lower extremity muscles, and areas with chronic muscle paresis have increased subcutaneous and intramuscular fat. 20,21 The current study did not find increased fat in the trunk and arms after adjustment for covariates, in contrast to Hayes-Allen and Tring’s study. 4 This difference may be a result of differences in measurement methodologies, distribution of neurosegmental levels, and/or adjustment for covariates in the current analysis.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…4 This is not surprising because myelomeningocele predominantly affects the lower extremity muscles, and areas with chronic muscle paresis have increased subcutaneous and intramuscular fat. 20,21 The current study did not find increased fat in the trunk and arms after adjustment for covariates, in contrast to Hayes-Allen and Tring’s study. 4 This difference may be a result of differences in measurement methodologies, distribution of neurosegmental levels, and/or adjustment for covariates in the current analysis.…”
Section: Discussioncontrasting
confidence: 85%
“…Because the level of lesion largely determines physical ability in children with myelomeningocele, it is not surprising that children with higher level lesions had more fat because of difficulty maintaining an energy balance, greater muscle paresis and atrophy, and increased adipocytes in the atrophied tissue. 21 However, since adjustment for covariates was not done in the neurosegmental subgroups, it remains unknown whether these differences, particularly the difference in trunk fat, are simply caused by greater obesity in the mid lumbar and above group. If this is the case, as in the main comparison of the combined neurosegmental levels to the comparison group, it would suggest that increased trunk fat is more closely associated with general obesity rather than myelomeningocele.…”
Section: Discussionmentioning
confidence: 99%
“…The qualitative feasibility of an alternative approach to accelerating fat-water separation with R2* modeling has been demonstrated in the skeletal muscle of a control subject (29). While there have been skeletal muscle studies with reports of fat fraction in type 2 diabetes, spina bifida, and rotator cuff injuries that have modeled R2* (27,30,31), in none of these studies was dystrophic muscle considered or was a particular significance ascribed to the R2* values obtained. Owing to the nonmonotonic relationship of R2* relaxation rates with disease progression, R2* is unlikely to be a useful trial end point, though it is essential for estimating fat fractions.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of more muscle-associated adipose tissue and less muscle volume are not unexpected given that myelomeningocele results in some degree of denervation of the lower extremity, which has been previously associated with decreased muscle volume as well as increased adipose tissue within and around muscles. 27,28 Interestingly, prior studies of obesity in spina bifida and paralyzed limbs have found higher skinfold thickness, indicating higher volumes of subcutaneous adipose, in the legs of children with myelomeningocele. 29,30 In contrast, this study found comparable subcutaneous adipose volumes between children with and without myelomeningocele.…”
Section: Discussionmentioning
confidence: 96%